If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + 1) = 2(x + 3) + -4 Reorder the terms: 4(1 + x) = 2(x + 3) + -4 (1 * 4 + x * 4) = 2(x + 3) + -4 (4 + 4x) = 2(x + 3) + -4 Reorder the terms: 4 + 4x = 2(3 + x) + -4 4 + 4x = (3 * 2 + x * 2) + -4 4 + 4x = (6 + 2x) + -4 Reorder the terms: 4 + 4x = 6 + -4 + 2x Combine like terms: 6 + -4 = 2 4 + 4x = 2 + 2x Solving 4 + 4x = 2 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 4 + 4x + -2x = 2 + 2x + -2x Combine like terms: 4x + -2x = 2x 4 + 2x = 2 + 2x + -2x Combine like terms: 2x + -2x = 0 4 + 2x = 2 + 0 4 + 2x = 2 Add '-4' to each side of the equation. 4 + -4 + 2x = 2 + -4 Combine like terms: 4 + -4 = 0 0 + 2x = 2 + -4 2x = 2 + -4 Combine like terms: 2 + -4 = -2 2x = -2 Divide each side by '2'. x = -1 Simplifying x = -1
| Z^2=8+6i | | 11-w=187 | | 4x+1=3(x+2)+2x | | 20.44=1.5x*x | | 2n^2+3x-9=0 | | 20x-5y=1.2 | | 0=1.5x*x | | 2/3x-5=61 | | 672=.08(x) | | 5-3(2x+2)=1-7x | | 1200-1/6 | | 5(x+3)=3x+35 | | 8r-28=6(3r+7) | | b^2=-5b | | 10g+2=2g+102 | | 6(z-4)=30 | | 3412x=18 | | 16^1/3x^3/5 | | 88=(-n+7) | | 7y=16x+30 | | (72/8)*9 | | S^2-6s-10=6 | | q=z-4n/b | | (12-8)+(9)+(25)=34 | | 3f+3w=17.70 | | 4x-4x^2=3 | | 15+p=7 | | 8x-5=9x+15 | | (6/x^5)^-2 | | 16*x^2-16x+3=0 | | 10-2q=-2+q | | .03x+.04(4y)=760 |